Value chain transformation - Hernandez, Ricardo; Belton, Ben; Reardon, Thomas; Hu, Chaoran; Zhang, Xiaobo; Ahmed, Akhter (International Food Policy Research Institute, 2019)
The majority of literature on aquaculture in Bangladesh focuses on “microsocioeconomics” and “value chains” (VCs) and tends to have a static perspective. However, this approach is at odds with several important emerging trends (Ali 1997; Ali, Haque, and Belton 2013). First, aquaculture is growing fast in Asia. From 1984 to 2014, Bangladesh’s farmed fish jumped from 124,000 metric tons to 1.96 million metric tons, increasing by 1,580 percent. As a result, aquaculture now accounts for 55 percent of Bangladesh’s fish supply, up from just 16 percent three decades ago (Bangladesh, DoF 1994, 1997, 2006, 2015). Second, there has been a rapid shift from home consumption (from one’s own pond) to purchasing farmed fish from the market—consumers of farmed fish got 92 percent of it via purchase from the market in 2010 versus 79 percent in 2000 (data extracted from BBS 2012). This implies that “commercial aquaculture” (which we define simply as fish farming output that is sold, with no specification of the farm size) has moved to be far more important than subsistence fish farming.